2018
DOI: 10.1111/anec.12584
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the influence of yogic methods on heart rate variability

Abstract: Low-frequency breathing (BR <12 cpm) plays a primary role in eliciting physiologically significant changes in HRV. By identifying a similarity in breathing oscillations of HR of FAG, YG, and PBG, the results recognize the coexistence of attention and breathing strategies and postulate their joint role in sustaining autonomic benefits, while effects induced by breathing alone on HRV could be attained even intermittently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Several works have studied the role of yoga in the overall health and a healthy lifestyle [15], [4], [5]. Also, yoga has been proposed in severe mental illnesses: it was found a reduction in general psychopathology ratings and an improvement in cognition and functioning in schizophrenic patients, and a significant benefit in reducing the severity of depressive symptoms [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several works have studied the role of yoga in the overall health and a healthy lifestyle [15], [4], [5]. Also, yoga has been proposed in severe mental illnesses: it was found a reduction in general psychopathology ratings and an improvement in cognition and functioning in schizophrenic patients, and a significant benefit in reducing the severity of depressive symptoms [16].…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that high frequency power was significantly higher in PRV analysis from NIVA than in heart rate variability (HRV) from ECG, suggesting that the NIVA signal may enhance measurement of parasympathetic activity. Some authors have studied the effect of yoga on the autonomic function via HRV analysis, showing an increase in parasympathetic activity [4], [5]. In this work, we want to study the effect of yoga on PRV measured with the NIVAband.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation